Trait convergence in photosynthetic nutrient‐use efficiency along a 2‐million year dune chronosequence in a global biodiversity hotspot. (28th March 2019) - Guilherme Pereira, Caio; Hayes, Patrick E.; O'Sullivan, Odhran S.; Weerasinghe, Lasantha K.; Clode, Peta L.; Atkin, Owen K.; Lambers, Hans
Abstract: The Jurien Bay dune chronosequence in south‐western Australia's biodiversity hotspot comprises sites differing in nutrient availability, with phosphorus (P) availability declining strongly with increasing soil age. We have explored the exceptionally high photosynthetic P‐use efficiency (PPUE) of Proteaceae in this region, triggering the question what the PPUE of co‐occurring species in other families might be along the Jurien Bay chronosequence. We explored how traits associated with PPUE, photosynthetic nitrogen (N)‐use efficiency (PNUE) and leaf respiration might converge along the chronosequence, and whether Proteaceae and non‐Proteaceae species differ in leaf traits associated with nutrient use. Seven to 10 species were sampled at three sites differing in nutrient availability (ranging from N‐ to P‐limited). Measurements of leaf light‐saturated photosynthesis and dark respiration were integrated with measurements of total N and P concentration in both mature and senesced leaves, and leaf mass per unit area (LMA). Contrary to what is known for other chronosequences, rates of photosynthesis and respiration did not decrease with increasing soil age and LMA along the Jurien Bay chronosequence. However, they increased when expressed per unit leaf P. Both N and P were used much more efficiently for photosynthesis on nutrient‐poor sites, in both Proteaceae and non‐Proteaceae species. Proteaceae had the fastest rate of photosynthesis per unit leaf P, followed by species that preferentially allocate P to mesophyll cells, rather than epidermal cells. Synthesis. Our results show that with declining soil P availability, photosynthetic P‐use efficiency of all investigated species from different families increased. Plants growing on the oldest, most nutrient‐impoverished soils exhibited similar rates of CO2 exchange as plants growing on more nutrient‐rich younger soils, and extraordinarily high photosynthetic P‐use efficiency. This indicates convergence in leaf traits related to photosynthetic nutrient use on severely P‐impoverished sites. Abstract : The Jurien Bay dune chronosequence in south‐western Australia comprises sites differing in nutrient availability, with phosphorus availability declining strongly with increasing soil age. We have explored the exceptionally high photosynthetic phosphorus‐use efficiency (PPUE) of Proteaceae in this region, triggering the question what the PPUE of co‐occurring species in other families would be. In this study, we analysed traits associated with gas exchange rates and photosynthetic nutrient‐use efficiency of multiple species across soil developmental stages. We show convergence in leaf traits related to PPUE on severely phosphorus‐impoverished sites.